Parametric Consideration While Designing Wells for Optimized Production - Zahoor, Muhammad Khurram; Haris, Muhammad (Pakistan Journal of Nutrition, 2013)
Transferring benefits of engineering knowledge and its advancements has always been a point of concern for the companies rather than providing direct information which can make general public capable of successfully solving various issues in the most economical way. Water is one of the major sources of nutrition and considered as utmost constituent of life. Therefore, in this study, petroleum engineering knowledge is discussed and implemented to calculate the water flow rate with reference to different surface pressures. Further investigating the influence of well trajectory (angle of inclination) and tubing/pipe diameter on water production rate. This research shows that as the angle of inclination varies from vertical; water production rate increases. It is also observed that change in diameter also have strong influence on water production rate. This study shows that the angle of inclination and diameter can be varied to increase the water production rate under prevailing conditions, to meet the demand of water supply and its utilization; as a major nutrition source and hence developing subsurface reservoirs for optimized production.